Milt-Egg Ratio in Artificial Fertilization of Pangasiid Catfish Injected by Gonadotropin Releasing Hormone-Analog (GnRH-a) and Domperidone Mixture - Subagja, J.; Sularto, .; Slembrouck, J. (Indonesian Society of Scientific Aquaculture (ISSA), 2003)
Study on the level of gonadotropin hormone treatments combined with latency time to induce ovulation in Pangasius djambal was conducted in the Research Instalation of Germ Plasm, Cijeruk, Bogor. This study was carried out to investigate the effect of GnRH-a and domperidone mixture on the milt production and fertilization rates of Pangasius djambal, and to determine the optimal milt-egg ratio required for artificial fertilization. Different doses of hormone i.e: 0,3; 0,5 and 0,7 ml kg